A leisure lifestyle among adults in Shah Alam / Mohamad Syafiq Arifin - Arifin, Mohamad Syafiq (Faculty of Education, 2014)
The purpose of this study was to investigate the leisure lifestyles among adults in Shah Alam. The three categories of lifestyle is active, passive and social leisure. The second category is the time adults spend for their leisure time. The last category is the leisure lifestyle among adults in Shah Alam. 50 respondents had been chosen randomly from several seksyen which include Seksyen 17, 18, 7, 2, and 13. This study use statistical analysis which is frequency and percentage. From the finding we found that adult in Shah Alam preferred to eat outside for general activities of their leisure time. For active leisure, they spend most of their time with sport and exercise. For passive leisure, they spend most of their time with relaxing at home. For social leisure, they choose hanging out with friend as their leisure activities. Adult in Shah Alam spend their leisure time at weekend. This study found that adult spends their leisure time about 4 to 6 hours per week. Adult in Shah Alam prefer to involve more for their leisure lifestyle is doing outdoor spaces activities. Besides that Most of adult in Shah Alam find out about the leisure activities they take part in through friends and family. In this study also focused on the event that adult in Shah Alam preferred to have more in their area. Most of the adult in Shah Alam prefer sport event to be held more in their area. Some suggestion need to take for future research which is increase the number of respondents, change the location to rural area, compare between gender and compare with socioeconomic status.